2009
DOI: 10.1200/jco.2008.20.8470
|View full text |Cite
|
Sign up to set email alerts
|

Phase II-I-II Study of Two Different Doses and Schedules of Pralatrexate, a High-Affinity Substrate for the Reduced Folate Carrier, in Patients With Relapsed or Refractory Lymphoma Reveals Marked Activity in T-Cell Malignancies

Abstract: A B S T R A C T PurposeTo determine the maximum-tolerated dose (MTD) and efficacy of pralatrexate in patients with lymphoma. Patients and MethodsPralatrexate, initially given at a dose of 135 mg/m 2 on an every-other-week basis, was associated with stomatitis. A redesigned, weekly phase I/II study established an MTD of 30 mg/m 2 weekly for six weeks every 7 weeks. Patients were required to have relapsed/refractory disease, an absolute neutrophil greater than 1,000/L, and a platelet count greater than 50,000/L … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
113
1
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(120 citation statements)
references
References 12 publications
2
113
1
4
Order By: Relevance
“…In other study, 14 (54%) of 26 patients with T-cell lymphoma showed CR (8 patients) and PR (6 patients). 122 Skin erosions has been reported to be in vivo evidence of pralatrexate-induced tumor cell apoptosis in the epidermis of a patient with ATL. 123 Further clinical trials are needed for the information on the efficacy of pralatrexate for ATL.…”
Section: Treatment Of Atlmentioning
confidence: 99%
“…In other study, 14 (54%) of 26 patients with T-cell lymphoma showed CR (8 patients) and PR (6 patients). 122 Skin erosions has been reported to be in vivo evidence of pralatrexate-induced tumor cell apoptosis in the epidermis of a patient with ATL. 123 Further clinical trials are needed for the information on the efficacy of pralatrexate for ATL.…”
Section: Treatment Of Atlmentioning
confidence: 99%
“…Interest in pralatrexate, a novel folate analog, for the treatment of PTCLs stemmed from a phase 1/2 study in patients with multiply relapsed and refractory hematologic malignancies suggesting that pralatrexate had a greater selectivity for TCLs. 41 The phase 2 PROPEL study recently evaluated pralatrexate in combination with vitamin B12 and folate in the treatment of relapsed/ refractory PTCL. By central review, the ORR was 29% (n ϭ 111) with a median PFS of 3.5 months and the median DoR was 10.5 months 42 (Table 4).…”
Section: Should Treatment Be Tailored For Specific Ptcl Subtype?mentioning
confidence: 99%
“…The ability to properly differentiate between PTCL types will help design targeted treatments and improve outcomes of these, frequently fatal, disorders. Other topics worth mentioning include results of phase II studies of up-front aggressive chemotherapy and autografting in patients with systemic PTCL [30,31], data suggesting that asparaginase is very active against NK-lymphomas [32] and the additions of pralatrexate and histone-deacetylase inhibitors vorinostat and romidepsin to the list of possible treatment modalities for PTCL and cutaneous T-cell lymphomas respectively [33][34][35]. Unfortunately, response rates to these novel agents are around a meager 30%.…”
Section: Peripheral T-cell Lymphomas (Ptcl)mentioning
confidence: 99%